Impact of inhomogeneous unsteady participating media in a coupled convection–radiation system using finite element based methods. (September 2021) - Avalos-Patiño, J.E.; Dargaville, S.; Neethling, S.J.; Piggott, M.D.
Highlights: A new non-uniform discretisation of the absorption distribution function (ADF) is introduced for gas radiation modelling. Better handling of energy groups with low Planck absorption coefficient. Non-uniform ADF improves the performance of the spherical harmonics method. Non-uniform ADF mitigates ray-effects that can result from the use of finite elements for the angular discretisation. Capability to handle inhomogeneous participating media which change in space, time, and absorption cross section values. Abstract: Combined convection–radiation is a common phenomenon in many engineering problems. A differentially–heated rectangular enclosure is a widely–used benchmark for testing numerical techniques developed for solving the coupled momentum and energy equations related to combined convection–radiation. Previous studies have tended to describe the phenomenon in cases using simplified characteristics for the participating media including the assumptions of: ( i ) uniform distribution, ( ii ) homogeneous cross section, ( iii ) grey gas radiation and ( iv ) under steady state conditions. The effects of an inhomogeneous unsteady participating media, e.g. composed of a mixture of gases, are arguably understudied. In this work the effect of an inhomogeneous unsteady participating media on combined convection–radiation inside a rectangular enclosure is considered, under both grey and non-grey gas modelling approaches involving a mixture of gases. A key novelty in this work is the inclusion of the ability to handle inhomogeneous participating media which change in space, time and absorption cross section values as a result of the convection–radiation coupling, allowing us to assess different gas modelling approaches. A global gas radiation model is used and a new non–uniform discretisation method for the absorption distribution function is introduced; this method allows a better handling of those energy groups in which the Planck absorption coefficient is low, improving the performance of the spherical harmonics method and mitigating ray–effects on finite elements in angle discretisation. The momentum and energy equations are solved numerically using finite element based discretisation methods. The radiative transfer equation is solved numerically using both spherical harmonics and finite elements for the angular discretisation, with their relative performance compared. The results highlight the importance that the characteristics of the participating media can have on the convection phenomenon and therefore on the resulting temperature field.